The Influence of Corporate Governance on Firm Financial Performance in India (Leadership, Education, Personality: An Interdisciplinary Journal, ISSN: 2524-6178, 2026)
Governance of corporations refers to the structures, policies, and procedures that are utilised in the process of directing and controlling operations inside an organisation. The major objective of this initiative is to connect the interests of diverse stakeholders, such as shareholders, management, and the wider community, with the intention of improving the performance of the organisation and increasing responsibility. The purpose of this abstract is to investigate the connection between corporate governance and the financial performance of a company, specifically focussing on the ways in which governance processes impact financial outcomes. Strong corporate governance frameworks, which are characterised by independent boards, transparent reporting, and equitable CEO compensation, have been found to have a positive correlation with greater financial performance, according to the findings. There is a correlation between effective governance and improved financial outcomes. Effective governance helps attenuate agency difficulties, decreases managerial entrenchment, and increases decision-making processes. When governance systems are inadequate, on the other hand, they frequently lead to decreased profitability, increased risk, and decreased confidence among investors.